2020
DOI: 10.1155/2020/8894331
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia muridarum Alleviates Colitis via the IL-22/Occludin Signal Pathway

Abstract: Ulcerative colitis (UC) is the most common inflammatory bowel disease, and its incidence has increased in recent years. Recent clinical and experimental data indicate that gut microbiota plays a pivotal role in the pathogenesis of UC. Chlamydia establishes a stable and persistent colonization in the gastrointestinal tract without apparent pathogenicity to gastrointestinal or extragastrointestinal tissues. However, the detailed effects of Chlamydia on the gastrointestinal tissue remain unknown. The primary aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…33 Experimentally, Cm has been shown to promote the expression of both IL-17 and IL-22. 15,62 IL-6 (associated with T-cell survival, downregulation of T regs , and as noted is protective against chlamydial infection) and IL-12 (which functions in tandem with IFNγ) were the principal elevated circulating pro-inflammatory cytokines. 65 We recently reported that mice deficient in IL-12 activity developed fulminant, fatal disease after Cm infection, supporting the important role this cytokine plays in response to infection with Cm.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…33 Experimentally, Cm has been shown to promote the expression of both IL-17 and IL-22. 15,62 IL-6 (associated with T-cell survival, downregulation of T regs , and as noted is protective against chlamydial infection) and IL-12 (which functions in tandem with IFNγ) were the principal elevated circulating pro-inflammatory cytokines. 65 We recently reported that mice deficient in IL-12 activity developed fulminant, fatal disease after Cm infection, supporting the important role this cytokine plays in response to infection with Cm.…”
Section: Discussionmentioning
confidence: 94%
“…These findings are consistent with previous oral experimental infections of Cm. 44,62 This phenotype may be attributable to the formation of non-replicating "aberrant bodies," downregulation of the immune response/development of host tolerance, and/or bacterial survival mechanisms. 44,69 Cm was only detected in epithelia and was generally restricted to epithelium overlying GALT, which became hyperplastic most likely a result of chronic immune stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other structural protein studied, Occludin, is a component of intercellular tight junctions which promotes this barrier's structural integrity [46,47]. Its expression is associated with the recovery of the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%